Effect of Contact Lens on Optical Coherence Tomography Imaging of Rodent Retina - Liu, Xiaojing; Wang, Chia-Hao; Dai, Cuixia; Camesa, Adam; Zhang, Hao F.; Jiao, Shuliang (Current eye research, 2013)
ABSTRACT Purpose: To evaluate the effect of powerless contact lens on improving the quality of optical coherence tomography imaging of rodent retina. Methods: A spectral-domain optical coherence tomography (SD-OCT) system was built for in vivo imaging of rodent retina. The calibrated depth resolution of the system was 3 µm in tissue. A commercial powerless contact lens for rat eye was tested in the experiments. For each rat eye, the retina was imaged in vivo sequentially first without wearing contact lens and then with wearing contact lens. The lateral resolution and signal-to-noise ratio of the OCT images with and without contact lens were compared to evaluate the improvement of image quality. Results: The fundus images generated from the measured 3D OCT datasets with contact lens showed sharper retinal blood vessels than those without contact lens. The contrast of the retinal blood vessels was also significantly enhanced in the OCT fundus images with contact lens. As high as 10 dB improvements in SNR was observed for OCT images with contact lens compared to the images of the same retinal area without contact lens. Conclusions: We have demonstrated that the use of powerless contact lens on rat eye can significantly improve OCT image quality of rodent retina, which is a benefit in addition to preventing cataract formation. We believe the improvement in image quality is the result of partial compensation of the optical aberrations of the rodent eye by the contact lens.